2022
DOI: 10.3389/fendo.2022.937049
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram model based on preoperative serum thyroglobulin and clinical characteristics of papillary thyroid carcinoma to predict cervical lymph node metastasis

Abstract: ObjectivePreoperative evaluation of cervical lymph node metastasis (LNM) in papillary thyroid carcinoma (PTC) has been one of the serious clinical challenges. The present study aims at understanding the relationship between preoperative serum thyroglobulin (PS-Tg) and LNM and intends to establish nomogram models to predict cervical LNM.MethodsThe data of 1,324 PTC patients were retrospectively collected and randomly divided into training cohort (n = 993) and validation cohort (n = 331). Univariate and multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
4
10
0
Order By: Relevance
“…In this study, the proportion of LLNM in PTC patients reached 59.1%, which was consistent with previous studies [3,11]. However, it is signi cantly higher than the proportion in some studies (about 10-20%) [9,10]. This may be due to the fact that many suspected PTC patients with a mass less than 1 cm and no obvious cervical lymph node metastasis currently take follow-up observation rather than active surgery.…”
Section: Factor Selection and Nomogram Constructionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the proportion of LLNM in PTC patients reached 59.1%, which was consistent with previous studies [3,11]. However, it is signi cantly higher than the proportion in some studies (about 10-20%) [9,10]. This may be due to the fact that many suspected PTC patients with a mass less than 1 cm and no obvious cervical lymph node metastasis currently take follow-up observation rather than active surgery.…”
Section: Factor Selection and Nomogram Constructionsupporting
confidence: 90%
“…Age has been considered as an independent risk factor for lymph node metastasis in PTC patients [10,12].…”
Section: Factor Selection and Nomogram Constructionmentioning
confidence: 99%
“…Some studies concluded that tumor size ≥1 cm is more likely to develop CNLNM than tumor size <1 cm ( 20 22 ), although several studies have not segmented tumors by 1 cm ( 23 29 ), and some studies concluded that larger tumor volume is more likely to develop CNLNM ( 30 , 31 ). In sum, CNLNM is generally more likely to occur with larger tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Most of the decisive factors involved in the published literature are independent and single, including age, gender, tumor size, and preoperative Tg. [41][42][43][44] Therefore, our study not only included the clinicopathological features closely related to LLNM but also introduced iodine nutrition-related markers, including SIC, TSH, and Tg.…”
Section: Discussionmentioning
confidence: 99%